Eksistensi dan Kontribusi Generasi Muda terhadap Keberlanjutan Kesenian Randai Minangkabau di Nagari Tiku Selatan Kabupaten Agam - Mohan Dika Afrilio; Asep Saepul Haris (INDO PUBLISHING, 2026)
This study aims to analyze the existence and contribution of young people to the sustainability of Minangkabau Randai performing arts in Nagari Tiku Selatan, Agam Regency. Randai is one of the traditional performing arts of Minangkabau that embodies cultural, educational, social, and customary values passed down from generation to generation. The rapid development of technology and the influence of globalization have posed challenges to the preservation of traditional arts, making the involvement of young people an essential factor in sustaining Randai. This study employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving Randai performers, traditional leaders, community leaders, and young people in Nagari Tiku Selatan. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that young people have a significant role in maintaining the sustainability of Randai through their participation as performers, musicians, trainers, and organizers of artistic activities. Furthermore, they contribute to the promotion and development of Randai through cultural events and the utilization of digital media. Nevertheless, the preservation of Randai still faces several challenges, including the influence of popular culture, the declining interest of some young people, and limited opportunities for appreciating traditional arts. This study concludes that the sustainability of Randai in Nagari Tiku Selatan is strongly influenced by the active participation of young people as agents of cultural preservation. Therefore, continuous support from the community, educational institutions, and government is necessary to strengthen the role of young people in preserving and developing Randai as a cultural heritage of the Minangkabau people.